Meningkatkan Hasil Belajar Peserta Didik dengan Pendekatan Pembelajaran Berdiferensiasi pada Mata Pelajaran IPAS Kelas IV SDN Besuk 1 - Putri, Erlita Herlyana; Prasasti, Mey Eka; Pratama, Yeheskiel; Damariswara, Rian; Lestari, Yeny Shirot Pudji (Jurnal Simki Postgraduate, 2025)
This study aims to improve the learning outcomes of fourth grade students in the subject of Natural and Social Sciences (IPAS) through a differentiated learning approach. The research method used is Classroom Action Research (CAR) which is implemented in three cycles. The study was conducted for three months involving 13 students and implemented in three cycles. Each cycle involves the stages of planning, implementing actions, observation, and reflection. The results of the study indicate that the differentiated learning approach can significantly improve student learning outcomes. In the initial cycle, the average student score was below the Minimum Completion Criteria (KKM), with learning completion only reaching 53.85%. After the implementation of differentiated learning, learning completion increased to 60% in cycle I, 65% in cycle II, and reached more than 75% in cycle III. This approach also increases student involvement and activity during the learning process.